2006
DOI: 10.1631/jzus.2006.b0800
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and paste properties of octenyl succinic anhydride modified early Indica rice starch

Abstract: Abstract:Octenyl succinic anhydride (OSA) modified early Indica rice starch was prepared in aqueous slurry systems using response surface methodology. The paste properties of the OSA starch were also investigated. Results indicated that the suitable parameters for the preparation of OSA starch from early Indica rice starch were as follows: reaction period 4 h, reaction temperature 33.4 °C, pH of reaction system 8.4, concentration of starch slurry 36.8% (in proportion to water, w/w), amount of OSA 3% (in propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
104
3
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(137 citation statements)
references
References 17 publications
24
104
3
6
Order By: Relevance
“…This is confirmation of higher reactivity of Golubica starch towards modification. Obtained values are, however, significantly higher than values reported by Song et al (2006) and Hui et al (2009) FT-IR spectra of starches bands originate mainly from the vibrational modes of amylose and amylopectin because these are the main components of starch (Amir et al 2011).…”
Section: Resultscontrasting
confidence: 64%
“…This is confirmation of higher reactivity of Golubica starch towards modification. Obtained values are, however, significantly higher than values reported by Song et al (2006) and Hui et al (2009) FT-IR spectra of starches bands originate mainly from the vibrational modes of amylose and amylopectin because these are the main components of starch (Amir et al 2011).…”
Section: Resultscontrasting
confidence: 64%
“…This finding is consistent with that reported by Song et al [19] who reported that at pH 9.5, side reaction (acetate starch hydrolysis) will be the dominant reaction. The optimized values of the reaction rate constants presented in Table 2 show that the value of mass transfer rate constant (Kcs) is smaller than chemical reaction constant (k).…”
Section: Effect Of Phsupporting
confidence: 93%
“…Song et al [19] reported that at pH 9.5, side reaction (acetate starch hydrolysis) will be the dominant reaction. Luo and Zhou [15] reported that the lower value of acetyl groups concentration in the starch acetate with increasing reaction time is mainly caused by hydrolysis of the starch ester (starch acetate).…”
Section: Effect Of Phmentioning
confidence: 99%
“…According to Song et al (2006), the increase in the transmittance value of starch pastes might be attributed to the introduction of carboxyl group, which retained the water molecules to form hydrogen bonds in the starch granules, thereby, increasing the clarity of starch pastes. Taking into account that, the formation of carboxyl groups after e-beam treatment of starch was suggested by the increased acidity of the irradiated starch pastes, we can consider this also as a factor which contributes to the increase of the clarity.…”
Section: Clarity and Its Stabilitymentioning
confidence: 99%